Pengenalan dan Pelatihan Global Biodiversity Information Facility (GBIF) pada Mahasiswa Program Studi Pendidikan Biologi Universitas Pendidikan Mandalika - Fajri, Siti Rabiatul; Hajiriah, Titi Laily; Armiani, Sucika; Sukri, Akhmad; Masiah, Masiah (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2022)
The service activity aims to introduce the importance of biodiversity data and train participants (Students of the Department of Biology Education) how to process data using the website from the Global Biodiversity Information Facility (GBIF) as a data source. This is done so that students are no longer confused in finding research data and looking for references on biodiversity data. This activity is intended for Department of Biology Education students who will take a thesis. The service implementation method consists of several stages, including: coordinating activities, implementing activities (introduction to GBIF), and training using the GBIF site. The service activity has been carried out for 2 days, namely Monday-Tuesday, 2-3 November 2020. The activity is carried out through zoom media due to the Covid-19 Pandemic condition. The activity was attended by 18 students from the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education, semester 7, as many as 18 students. The first day of activities, November 2, 2020 at 14.00 WITA, began with the introduction of GBIF to students of the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education. Then on the second day on November 3 at 09.00 WITA, the Service Team provided training on the use of GBIF and provided examples of thesis titles that could be done using the GBIF website. GBIF was first introduced to students of the Department of Biology Education, Faculty of Applied Science and Engineering, Mandalika University of Education, and students were very enthusiastic to know that there was a site that could help them in finding research data and looking for references on biodiversity data to compose their thesis.